Socialization of the Healthy School Movement in Early Childhood Education - Lestariningrum, Anik; Khan, Rosa Imani; Munir, Salma Alfianza (Dimar : Jurnal Pengabdian Masyarakat, 2025)
This community service aims to enhance the understanding and implementation of the Healthy School Movement (Gerakan Sekolah Sehat, GSS) in Early Childhood Education (Pendidikan Anak Usia Dini, PAUD) in Kediri Regency. The primary issue is the low awareness of healthy lifestyle practices in PAUD settings, impacting children’s health and development. The approach included educational material delivery, hygiene practice demonstrations, and interactive discussions involving 90 educators, supervisors, and PAUD inspectors. Conducted in partnership with the Kediri Regency Education Office, the program ensured relevance and sustainability. Results showed a 94.4% increase in understanding of the five GSS pillars (nutrition, physical health, immunization, mental health, and environment), 88% readiness to implement healthy practices, and the formation of PAUD Healthy School Teams in 72 schools. The program is expected to foster a healthy educational environment supporting optimal early childhood development. Follow-up actions include advanced training and school facility improvements.